Information Systems Design and Intelligent Applications Proceedings of Third International Conference INDIA 2016, Volume 1 - Satapathy, Suresh Chandra; Mandal, Jyotsna Kumar; Udgata, Siba K.; Bhateja, Vikrant; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
The third international conference on INformation Systems Design and Intelligent Applications (INDIA - 2016) held in Visakhapatnam, India during January 8-9, 2016. The book covers all aspects of information system design, computer science and technology, general sciences, and educational research. Upon a double blind review process, a number of high quality papers are selected and collected in the book, which is composed of three different volumes, and covers a variety of topics, including natural language processing, artificial intelligence, security and privacy, communications, wireless and sensor networks, microelectronics, circuit and systems, machine learning, soft computing, mobile computing and applications, cloud computing, software engineering, graphics and image processing, rural engineering, e-commerce, e-governance, business computing, molecular computing, nano-computing, chemical computing, intelligent computing for GIS and remote sensing, bio-informatics and bio-computing. These fields are not only limited to computer researchers but also include mathematics, chemistry, biology, bio-chemistry, engineering, statistics, and all others in which computer techniques may assist.
Chapter 1. Study and Analysis of Subthreshold Leakage Current in Sub-65 nm NMOSFET -- Chapter 2. Implementations of Secure Reconfigurable Cryptoprocessor: A Survey -- Chapter 3. Mitigating & Patching System Vulnerabilities Using Ansible: A Comparative Study of Various Configuration Management Tools for IAAS Cloud -- Chapter 4. Adaptive Fractal Image Compression Based on Adaptive Thresholding in DCT Domain -- Chapter 5. Improved Resource Exploitation by Combining Hadoop Map Reduce Framework with VirtualBox -- Chapter 6. Density Based Outlier Detection Technique -- Chapter 7. Systematic Evaluation of Seed Germination Models: A Comparative Analysis -- Chapter 8. Business Modeling Using Agile -- Chapter 9. An efficient Hybrid Encryption Technique Based on DES and RSA for Textual Data -- Chapter 10. Application of Machine Learning on Process Metrics for Defect Prediction in Mobile Application -- Chapter 11. Automatic Insurance and Pollution Challan Generator System in India -- Chapter 12. Effectively Implementation of KNN-Search on Multidimensional Data Using Quadtree -- Chapter 13. Edge Detectors Based Telegraph Total Variational Model for Image Filtering -- Chapter 14. Cloud Based K-means Clustering Running as a MapReduce Job for Big Data Healthcare Analytics Using Apache Mahout -- Chapter 15. Symbolic Decision Tree for Interval Data - An Approach towards Predictive Streaming and Rendering of 3D Models -- Chapter 16. Predictive 3D Content Streaming Based on Decision Tree Classifier Approach -- Chapter 17. Quantitative Characterization of Radiographic Weld Defect Based on the Ground Truth Radiographs made on a Stainless Steel Plates -- Chapter 18. Research and Topology of Shunt Active Filters for Quality of Power -- Chapter 19. Development Of 3d High Definition Endoscope System -- Chapter 20. Excel Solver for Deterministic Inventory Model: INSOLVER -- Chapter 21. DSL Approach for Development of Gaming Applications -- Chapter 22. Digital Forensic Architecture for Cloud Computing Systems: Methods of Evidence Identification, Segregation, Collection and Partial Analysis -- Chapter 23. Brushing - An Algorithm for Data Deduplication -- Chapter 24. A New Approach for Integrating Social Data into Groups of Interest -- Chapter 25. Estimation of Shape Parameter of the Radial Distribution of Cosmic Ray Shower Particles -- Chapter 26. Network Security in Big Data: Tools and Techniques -- Chapter 27. Design of Ripple Carry Adder Using 2-Dimensional 2-Dot 1-Electron Quantum-Dot Cellular Automata -- Chapter 28. Advanced Congestion Control Techniques for MANET -- Chapter 29. A Method of Baseline Correction for Offline Handwritten Telugu Text Lines -- Chapter 30. A Technique for Prevention of Derailing and Collision of Trains in India -- <Chapter 31. Temporal Scintimetric Characterization of Skeletal Hotspots in Bone Scan by Dr. V. Siva's Retention Ratio -- Chapter 32. Executing Hive Queries on 3-NODE Cluster and AWS Cluster- Comparative Analysis -- Chapter 33. Performance of Speaker Independent Language Identification System under Various Noise Environments -- Chapter 34. Multi-level Fusion of Palmprint and Dorsal hand Vein -- Chapter 35. A Comparative Study on Multi-view Discriminant Analysis and Source Domain Dictionary Based Face Recognition -- Chapter 36. Mining Maximal Efficient Closed Item Sets without any Redundancy -- Chapter 37. An Interactive freehand ROI Tool for Thyroid Uptake studies Using Gamma Camera -- Chapter 38. Literature Survey on Intrusion Detection Systems in MANETs -- Chapter 39. Apply of Sum of Difference Method to Predict Placement of Students' Using Educational Data Mining -- Chapter 40. Robust Color Image Multi-thresholding Using Between-class variance and Cuckoo Search Algorithm -- Chapter 41. Social Media: A Review -- Chapter 42. Bayesian-Fuzzy GIS Overlay to Construe Congestion Dynamics -- Chapter 43. A Hybrid Clustering Technique to Improve Big Data Accessibility Based on Machine Learning Approaches -- Chapter 44. Efficient Iceberg Query Evaluation Using Compressed Bitmap Index Technique in Distributed Databases -- Chapter 45. Unique Identifier System Using Aneka Platform -- Chapter 46. A Novel Graphical Password Authentication Mechanism for Cloud Services -- Chapter 47. A Conceptual Framework for Big Data Implementation to Handle Large Volume of Complex Data -- Chapter 48. Path Reliability in Automated Test Case Generation Process -- Chapter 49. A Study on Wii Remote Application as Tangible User Interface in Elementary Classroom Teaching -- Chapter 50. Enhanced Understanding of Education Content Using 3D Depth Vision -- Chapter 51. AHP-based Ranking of Cloud-Service Providers -- Chapter 52. Hardware Prototyping for Enhanced Resilient On-board Navigation Unit -- Chapter 53. Web Data Analysis Using Negative Association Rule Mining -- Chapter 54. Cloud Based Thermal Management System Design and Its Analysis -- Chapter 55. ICC Cricket World Cup Prediction Model -- Chapter 56. Towards distributed Solution to the State Explosion Problem -- Chapter 57. Real Time Bus Monitoring System -- Chapter 58. High Performance DFT Architectures Using Winograd Fast Fourier Transform Algorithm -- Chapter 59. Dynamic Voltage Restorer Based on Neural Network and Particle Swarm Optimization for Voltage Mitigation -- Chapter 60. Analysis of Norms in Adaptive Algorithm on Application of System Identification -- Chapter 61. SKT: A New Approach for Secure Key Transmission Using MGPISXFS -- Chapter 62. A Comparative Study of Different Approaches for the Speaker Recognition -- Chapter 63. A Time Efficient Leaf Rust Disease Detection Technique of Wheat Leaf Images Using Pearson Correlation Coefficient and Rough Fuzzy C-Means -- Chapter 64. Task Scheduling Algorithms with Multiple Factor in Cloud Computing Environment -- Chapter 65. The State of the Art in Software Reliability Prediction: Software Metrics and Fuzzy Logic Perspective -- Chapter 66. An Indexed Approach for Multiple Data Storage in Cloud -- Chapter 67. Design New Bi-orthogonal Wavelet Filter for Extraction of Blood Vessels and Calculate the Statistical Features -- Chapter 68. Demand Side Management Using Bacterial Foraging Optimization Algorithm -- Chapter 69. An Optimized Cluster Based Routing Technique in VANET for Next Generation Network -- Chapter 70. AgroKanti: Location-aware Decision Support System for Forecasting of Pests and Diseases in Grapes -- Chapter 71. A Unified Modeling Language Model for Occurrence and Resolving of Cyber Crime -- Chapter 72. Cross Lingual Information Retrieval (CLIR): Review of Tools, Challenges and Translation Approaches -- Chapter 73. Minimizing the Cost of Losses Due to Cyber Attack through B. B. (Branch and Bound) Technique -- Chapter 74. Denoising Knee Joint Vibration Signals Using Variational Mode Decomposition -- Chapter 75. Data Size Reduction and Maximization of the Network Lifetime over Wireless Sensor Network.
Keywords: Computational intelligence; Signal processing; Artificial intelligence; Computational Intelligence; Signal, Speech and Image Processing; Artificial Intelligence